Advancements in urban water management and ecological restoration technologies: Frameworks, challenges, and emerging trends - Sitong Zou; Yucong Zheng; Mawuli Dzakpasu; Qian Li; Ting Cao; Liping Zhao; Tianfu Wu; Dongfu Zhang; Yunze Chai; Rong Chen (Journal of Water Process Engineering, 2025)

Field verification of the surface renewal method for evapotranspiration measurement in arid agricultural area: The uncertainty of calibration parameter - Zhen Wang; Nanjuan Zheng; Bingbing Jiang; Yao Rong; Xin Li; Peijin Wu; Weishu Wang; Chenglong Zhang; Zailin Huo (Journal of Hydrology, 2025)

Influence of multiple environmental factors on plastics in facility agriculture soils at a national scale, China - Guiming Liu; Sashuang Rong; Cun Liang; Yang Yang; Xuyang Zheng; Shutao Wang; Shiming Su; Zhenyong Li; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Assessment of hydrogen adsorption capacities on low-maturity shales for geological storage applications: a lattice density functional theory approach - Rong Zheng; Ke Hu; Ying Wu; Xiaochen Li; Guanhua Li (Fuel, 2025)

Seismic mitigation and configuration-based performance study on particle tuned mass damper applied to transmission tower-line system - Kunjie Rong; Junrong Gong; Zheng Lu; Li Tian; Yelei Shen; Mengyao Zhou (Engineering Structures, 2025)

Sources and formation characteristics of atmospheric water-soluble organic carbon in North China: Implications from a one-year background observation - Jing Yu; Rong Sun; Yuchen Li; Xuehua Yin; Zheng Zong; Ling Sun; Chongguo Tian (Atmospheric Environment, 2025)

Erosion rates of yardang landforms downstream of the Peacock River, NW China - Bai Youliang; Bo Li; Jinhong Rong; Hui Chen; Jinming Zheng; Jianshe Liu; Tan Bao; Jiangnan Jin; Chuan Wang (Journal of Sedimentary Environments, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Spon2 knockdown suppresses the phenotype of house dust mite-induced allergic asthma in mice and cells - Haihan Zheng; Shenggang Ding; Daoxiang Rong; Ting Li; Mei Xiong (Immunologic Research, 2025)

Achnatherum inebrians tolerance to salt stress is linked with the changes of rhizosphere microbiome and root exudates - Ronggui Liu; Chao Wang; Jie Jin; Xiaoshan Zhu; Lanlan Chen; Yang Yang; Rong Zheng; Kamran Malik; Jianfeng Wang; Chunjie Li (Soil Ecology Letters, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Sustainable bipolar membranes with three-dimensional flower-like spherical MgAl-layered double hydroxides doped quaternized chitosan for accelerated water dissociation and durability - Ming Li; Jinyun Xu; Hongze Li; Xiaoqing Wang; Shijie Shang; Xiaoyan Wang; Sijia He; Yanyan Ji; Li Yang; Rong Kuang; Chenxin Hu; Wenju Zhu; et al. (Desalination, 2025)

The multimodal anti-tumor effect of cisplatin nanoparticles loaded with bacterial antibodies in combination with radiotherapy: targeting hypoxic tumor and reshaping of the immune microenvironment - Min Wu; Zhouxue Wu; Weizhou Wang; Yunxue Zheng; Hongxia Li; Yuan Huang; Liping Deng; Yingqi Gu; Jinfeng Rong; Xiaoyin Zhang; Wen Yang; Yue Chen; et al. (Chemical Engineering Journal, 2025)

Gut microbiota-metabolite dynamics in Sebastes schlegelii following Vibrio harveyi infection - Yindong Gu; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Zhiqi Zhang; Xiaojun Rong; Meijie Liao; Lei Qin; Bin Li; Zheng Zhang (Aquaculture International, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

A ZnO packaged MEMS hydrogen sensor for reliable SIBO breath analysis with anti-H2S interference - Zheng Yang; Qian Rong; Wei Zhang; Xintao Fan; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2025)

Adipose-bone microenvironment precision-regulation nanoplatform: A visualized mild photothermal-enhanced osteogenesis strategy for osteonecrosis of the femoral head - Jinxuan Li; Mengting Gao; Yuhang Wang; Rong Dai; Qi Liu; Shutong Wu; Jian Zhang; Hua Wu; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Temporal-spatially metabolic reprogramming rewires the landscape of H3K27 acetylation to enable the initiation of liver regeneration - Qi Zheng; Xiaojiaoyang Li; Fanghong Li; Zhenyu Xu; Yajie Cai; Changmeng Li; Xiaoyong Xue; Shuo Li; Rong Sun; Guifang Fan; Jianzhi Wu; Jiaorong Qu; et al. (Science Bulletin, 2025)

Nonlinear numerical investigation and performance analysis of an oscillating-body wave energy converter integrated with a floating breakwater - Xiongbo Zheng; Wenbin Lai; Jialong Li; Sizhang Rong; Hongkun Yang (Ocean Engineering, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Cambrian mid-ocean ridge basalt-like mafic rocks and associated boninites in the Dachadaban ophiolite from the North Qilian Block, northwest China: Petrogenesis and implications for back-arc extension - De-Chao Li; Xi-Jun Liu; Xiao Liu; Gang Chen; Qi Song; Hao Tian; Zheng-Lin Li; Peng-De Liu; Rong-Guo Hu (Geochemistry, 2025)

Hydrogel pads loaded with essential oil contribute to maintaining blueberry quality after transportation - Yuxuan Li; Haifeng Rong; Sixu Lin; Yaohui Zheng; Ling Yang; Bingxin Sun; Yunhe Zhang; Yufeng Xu; Xuerui Yan (Food Packaging and Shelf Life, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

A leapfrog improvement in N-butanol detection achieved through single atom catalysts Co-N-C - Luhan Cheng; Zhixiang Yuan; Rong Wu; Zhou Li; Jun Zheng; Jiming Song (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Potential genetic characteristics of Bacillus velezensis LZUR632 enhance the resistance of Achnatherum inebrians to Cd stress by altering rhizosphere microbial community composition and functional genes - Jie Jin; Chao Wang; Ronggui Liu; Rong Zheng; Maohua Deng; Jianfeng Wang; Chunjie Li (Plant and Soil, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

An end-to-end maturity prediction and hierarchical counting method for cherry tomatoes - Jiacheng Rong; Xianjun Li; Wanli Zheng; Tongqiang Chen; Ting Yuan; Pengbo Wang; Wei Li (Biosystems Engineering, 2025)

Experimental and numerical study on the seismic mitigation performance of particle dampers on transmission tower-line system - Zheng Lu; Yelei Shen; Mengyao Zhou; Kunjie Rong; Li Tian (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Automatic morphologic classification of Martian craters using imbalanced datasets of Tianwen-1’s MoRIC images with deep neural networks - Qifang Zheng; Rong Huang; Yusheng Xu; Fangzhao Zhang; Changjiang Xiao; Luning Li; Xiaohua Tong (Planetary and Space Science, 2025)

3,4-seco-Prenyllabdane sesterterpenoids and 3,4-seco-labdane diterpenoids with Zika virus inhibitory potential from Callicarpa nudiflora - Xue-Wen Wu; Guan-Rong Qiao; Xue-Rong Zhao; Qi Li; Muhammad Aurang Zeb; Xiao-Li Li; Chang-Bo Zheng; Wei-Lie Xiao (Phytochemistry, 2025)

Chemical constituents of the deep-sea-derived fungus Purpureocillium lilacinum XIA-18 and their chemotaxonomic significance - Bao-Fu Li; Yuan Wang; Zheng-Biao Zou; Rong Chao; Tai-Zong Wu; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2025)

Global synthesis on the responses of microbial- and plant-derived carbon to conservation tillage - Yalin Yu; Li Li; Jinkang Yang; Yinan Xu; Ahmad Latif Virk; Jie Zhou; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Plant and Soil, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Spatio-temporal dynamic characteristics of the substitution effect of ride-hailing travel and its multi-activity network: a case study of Chengdu - Zhicheng Zheng; Yang Li; Peijun Rong; Lijun Zhang; Yaochen Qin; Gangjun Liu (Journal of Transport Geography, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Reductive dechlorination of 1,1,2-trichloroethane in groundwater by zero valent iron coupled with biostimulation under sulfate stress: Differences and potential mechanisms - Naijin Wu; Yi Li; Yizhou Liu; Yangfan Feng; Wenbo Fei; Tianwen Zheng; Liming Rong; Nan Luo; Yun Song; Wenxia Wei; Peizhong Li (Environmental Research, 2025)

Molecular Insight Into the Hydrolysis of Phthalate Esters by a Family IV Esterase - Zhen Rong; Li‐Guo Hong; Ying‐Yi Huo; Jixi Li; Dao‐Qiong Zheng; Yang Ha; Jeffrey Fan; Xue‐Wei Xu; Yue‐Hong Wu (Environmental Microbiology, 2025)
Phthalate esters (PAEs) are prevalent environmental contaminants, with their biodegradation efficiently driven by microorganisms through ester bond hydrolysis. This study investigates the mechanism of Poc14, a novel family IV esterase, using x‐ray crystallography, bioinformatics, biochemistry and site‐directed mutagenesis. Phylogenetic analysis classifies Poc14 as a family IV esterase with conserved catalytic motifs crucial for its activity. Poc14 retains over 80% activity at 50°C for 4 h and tolerates up to 5% methanol or DMF, though surfactants like Tweens inhibit its function. Poc14 activity is independent of metal ions, and the addition of EDTA further enhances its activity by approximately 130%. The 1.8 Å crystal structure reveals a CAP domain and two substrate channels. Enzyme assays show Poc14 hydrolyses short‐chain diethyl phthalate (DEP) ( K m = 0.068 mM, V max = 9975 μM/min/mg) but not long‐chain di(2‐ethylhexyl) phthalate (DEHP) due to steric hindrance. Molecular docking assessed Poc14's potential to hydrolyse DEP and DEHP after residue mutations, resulting in the Poc14‐AAG variant. Poc14‐AAG could hydrolyse one bond of DEHP and diester bonds of DEP. Our study positions Poc14 as a promising enzyme for environmental remediation, with potential for optimising DEHP degradation and exploring dimerisation effects.

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Ultrastructure and sense organs of ovipositors in the phytophagous gall-maker pest Ophelimus maskelli (Hymenoptera: Eulophidae) and its parasitoid, Closterocerus chamaeleon (Hymenoptera: Eulophidae) - Yuan-Hao Li; Yu-Yue Huang; Yu-Chun Huang; Xiao-Rong Tang; Wen-Ting Huang; Xia-Lin Zheng (Journal of Asia-Pacific Entomology, 2025)

Regulating the gradient water distribution via hydro-philic/phobic compositional design in ionogels for stable zinc ion batteries - Rong Zheng; Nan Jiang; Baojun Wang; Chengyi Hou; Qinghong Zhang; Hongzhi Wang; Yaogang Li; Kerui Li (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Gut microbiota and serum metabolomics unveil the role of Phellinus ribis polysaccharides in improving Alzheimer's disease symptoms in senescence-accelerated mice - Zhiyuan Zhang; Shuai Wang; Rong Rong; Guoying Zhang; Zheng Li; Yuanyuan Li; Rongxiang Wang; Yuhong Liu; Kejian Li (Metabolic Brain Disease, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A millennial record of lake ecosystem responses to climatic variability in the Yellow River Source Area - Jianan Zheng; Rong Wang; Hanxiao Zhang; Shouliang Huo; Jingjing Li; Yanjie Zhao; Ji Shen (Quaternary Science Reviews, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Combination of extrusion and bamboo leaf flavonoids modulates in vitro maize starch digestion: Insight into the molecular mechanisms and multi-scale structure - Jiong Zheng; Rong Hu; Yuming You; Xiaojing Li; Fusheng Zhang; Liangru Wu (Food Chemistry, 2025)

Unraveling the impact of micro- and nano-sized polymethyl methacrylate on gut microbiota and liver lipid metabolism: Insights from oral exposure studies - Peng Chen Zheng; Xin Qiang Pan; Yi Jiong Zhou; Keng Po Lai; Rong Li; Xiao Xi Zhang (Environmental Pollution, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Interfacial structure design enables rapid reaction kinetics for high-voltage NCM 613 cathodes - Yuan Xiao; Rong Gu; Tingting Zheng; Bowen Chang; Qiaoxia Li; Shuaiqi Gong; Xin Wei; Qunjie Xu; Yulin Min (Chemical Engineering Journal, 2025)

A comparative study of four color measurement methods for soil color identification and related properties prediction - Yuanyuan Du; Fengjin Kang; Zhangke Huang; Luyi Wang; Ya Zhang; Decheng Li; Guanghui Zheng; Rong Zeng (Computers and Electronics in Agriculture, 2025)

Effect of scenting process on the taste profile of jasmine green tea and the potent bitterness-enhancing compound in jasmine flowers - Jia-Ying Chen; Wen-Wen Luo; Wen-Xuan Li; Ya-Nan Zheng; Xin-Qiang Zheng; Jian-Liang Lu; Yue-Rong Liang; Jian-Hui Ye (Food Research International, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Crop straw converted to biochar increases soil organic carbon but reduces available carbon - Li Li; Jinkang Yang; Yalin Yu; Awais Shakoor; Ahmad Latif Virk; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (European Journal of Agronomy, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Opposing island biogeographic effects of turnover and nestedness on beta-diversity of soil faunal communities between woodland and deforested grassland - Zengyan Li; Zengke Zhang; Anna Yang; Sufeng Pan; Junyong Zheng; Ling Mou; Wensheng Chen; Tian Zhang; Liyi Zhou; Wenhui You; David A. Wardle; En-Rong Yan (Applied Soil Ecology, 2025)

Effects of crop rotation on plant- and microbial-derived carbon within particulate and mineral fractions in paddy soils - Yalin Yu; Ningxuan Zhu; Ying Ren; Menghan Dong; Guofeng Sun; Ahmad Latif Virk; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Agriculture, Ecosystems & Environment, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Advancements in the development of porous nanomaterials for CO2 capture of deep decarbonization: Pore structure and chemical group optimization - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Lin Guo; Youming Zhu; Jinfeng Mei; Jian Rong; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Amine-impregnated elastic carbon nanofiber aerogel templated by bacterial cellulose for CO2 adsorption and separation - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Identification of Boveria labialis parasitism in the respiratory tree of the Cultured Sea cucumber, Apostichopus japonicus - Wenyue Hao; Xiaojun Rong; Meijie Liao; Bin Li; Yingeng Wang; Jianlong Ge; Jinjin Wang; Zheng Zhang; Yongxiang Yu (Aquaculture, 2025)

The key pathogenic factor GcSP2 of Geotrichum citri-aurantii plays an important role in disrupting citrus metabolism and immunity - Rong Liu; Haoxiang Zheng; Di Wang; Haijue Zhang; Yan Wu; Xue Li; Zhengfeng Liu; QingJun Kong; Xueyan Ren (Postharvest Biology and Technology, 2025)

Variation in microbial communities and network ecological clusters driven by soil organic carbon in an inshore saline soil amended with hydrochar in Yellow River Delta, China - Hui Yao; Yadong Cheng; Qingxian Kong; Xiao Wang; Ziguo Rong; Yue Quan; Xiangwei You; Hao Zheng; Yiqiang Li (Environmental Research, 2025)

Effective periodate activation of direct Z-scheme g-C3N4/Cu2O heterojunction for photocatalytic norfloxacin degradation, anti-bacterial activity and toxicity assessment - Qinyi Gu; Jian Rong; Yuzhe Zhang; Xudong Zheng; Ziyao Zhou; Zhongyu Li; Song Xu (Chemical Engineering Journal, 2025)

Bismuth/manganese-doped carbon dots in calcium phosphate matrix: Dynamic conformational nanoparticles enhancing tumor accumulation, deep penetration, and radiosensitivity - Jiahao Liu; Qingnian Li; Hanyu Tu; Jie Feng; Xiaofei Fan; Ze Mi; Hongpei Han; Xiaoqian Ma; Qi Liang; Zheng Zhang; Hongshuai Hou; Pengfei Rong; et al. (Chemical Engineering Journal, 2025)